The importance of drug metabolites synthesis: the case-study of cardiotoxic anticancer drugs - Hrynchak I. (2017)
Anticancer drugs are presently guarantying more survivors as a result of more powerful drugs or combinations of drugs used in therapy. Thus, it has become more crucial to study and overcome the side effects of these therapies. Cardiotoxicity is one of the most relevant side effects on the long-term cancer survivors, because of its high social and economic impact. Drug metabolism can result in active metabolites or toxic metabolites that can lead to important side effects. The metabolites of anticancer drugs are possible culprits of cardiotoxicity; however, the cardiotoxicity of many of the metabolites in several drug classes was not yet suitably studied so far. On the other hand, the use of prodrugs that are bioactivated through metabolism can be a good alternative to obtain more cardio safe drugs. In this review, the methods to obtain and study metabolites are summarized and their application to the study of a group of anticancer drugs with acknowledged cardiotoxicity is highlighted. In this group of drugs, doxorubicin (DOX, 1), mitoxantrone (MTX, 2), cyclophosphamide (CTX, 3) and 5-fluorouracil (5-FU, 4) are included, as well as the tyrosine kinase inhibitors, such as imatinib (5), sunitinib (6) and sorafenib (7). Only with the synthesis and purification of considerable amounts of the metabolites can reliable studies be performed, either in vitro or in vivo that allow accurate conclusions regarding the cardiotoxicity of anticancer drug metabolites and then pharmacological prevention or treatment of the cardiac side effects can be done. © 2017 Informa UK Limited, trading as Taylor & Francis Group.